Socioeconomic conditions, gestacional risk and importance of relationship between obstetrician and high risk pregnant women - Bruna Teixeira dos Santos, Bruna Karoline Santos Melo Monteiro, José Gilmar Costa Santos, Renata Sousa de Santana Silva, Lígia Mara Dolce de Lemos, Júlia Maria Gonçalves Dias (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v5i3.5441